Characterization of Organic Polymer Monolith Columns Containing Ammonium Quarternary As Initial Study For Capillary Chromatography - Aster Rahayu; Siti Jamilatun; Joni Aldilla Fajri; Lee Wah Lim (Elkawnie: Journal of Islamic Science and Technology, 2021)
Abstract: The polymerization process with a simple step has become the centre of attention of several researchers. Various polymers have been developed, although in general, they use polymerization with a post-modification method. A quaternary ammonium monolith organic polymer has been prepared using a simple single thermal method in this research. 2-(Methacryloyloxy)-N,N,N-trimethylethanaminium chloride was as the monomer, and ethylene dimethacrylate was as crosslinker. The polymerization proceeded in fused-silica capillary (100 mm, 0.32 mm i.d. x 0.45 mm o.d.) using a one-pot approach method. To achieve the perfect macropores, isopropyl alcohol, PEG 400, and ethanol were used as porogen. Characterization of the surface morphology was carried out using a Scanning Electron Microscope (SEM), and the existence of an amine group was characterized by Fourier Transform Infrared Spectroscopy (FTIR). The distribution size of pores in the polymer was in the range of 1.29 to 3.33 µm.